Mulsa Organik: Pengaruhnya terhadap Lingkungan Mikro, Sifat Kimia Tanah dan Keragaan Cabai Merah di Tanah Vertisol Sukoharjo pada Musim Kemarau - Puji Harsono (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2012)
ABSTRACTRed chilli is commercial crop and has high economic values. Experiments were conducted to improve red chilli’s cultivation technique, by applying organic mulches to increase plant growth and yield. The experiment was set up in a completely randomized block design with three replications to evaluate the effects of organic mulches on microclimate, soil chemical properties, red chilli growth and yield. Mulch treatment consisted of silver-black polyethylene plastic, rice straw, rice husk, corn litter and without mulch as a control. The application of organic mulches at the rate of 6 ton ha-1in the dry season increased soil temperature, soil moisture, cation exchange capacity, pH, C organic, soil organic matter, N total, K availability and C/N ratio. The application of organic mulches in dry season increased plant growth in terms of number of dichotome branches, leaf area, and dry weight of plant, net assimilation rate, relative growth rate, fruit length and better fruit yields. The highest production was achieved by rice straw, i.e, 1.29 kg fruit fresh weight per plant. Plant treated with organic mulches produced fruit per plot 18% greater than those treated with plastic polyethylene.Keywords: cation exchange capacity, leaf area, growth, yieldABSTRAKCabai merah merupakan tanaman komersial dan memiliki nilai ekonomi yang tinggi. Percobaan dilakukan untuk memperbaiki teknik budidaya cabai merah dengan pengaplikasian mulsa organik untuk meningkatkan pertumbuhan dan hasil tanaman. Percobaan disusun dalam rancangan kelompok lengkap teracak dengan 3 ulangan untuk mengevaluasi pengaruh mulsa organik terhadap iklim mikro, sifat kimia tanah, pertumbuhan dan hasil cabai merah. Mulsa yang digunakan adalah plastik polietilen hitam perak, jerami padi, sekam padi, serasah jagung dan tanpa gulma sebagai kontrol. Aplikasi mulsa organik adalah sebesar 6 ton/ha pada musim kering meningkatkan suhu tanah, kelembaban tanah, kapasitas tukar kation, pH, C organik, bahan organik tanah, N total, ketersediaan K dan C/N rasio. Aplikasi mulsa organik pada musim kering meningkatkan pertumbuhan tanaman dilihat dari jumlah cabang dikotomus, luas area daun, bobot kering tanaman laju asimilasi bersih, laju pertumbuhan relatif, panjang buah dan hasil buah yang lebih baik. Produksi tertinggi diperoleh pada perlakuan mulsa organik jerami padi dengan bobot buah segar, sekitar 1.29 kg per tanaman. Tanaman dengan perlakuan mulsa organik meng hasilkan buah per plot 18% lebih besar dibandingkan tanaman dengan perlakuan mulsa plastik polietilen hitam perak.Kata kunci : kapasitas tukar kation, area daun, pertumbuhan, hasil